Geomagnetic Conjugacy between the Antarctic and the Arctic - Nagata, Takesi (1967)
P(論文) Along a tube of force of the geomagnetic field, charged particles such as electrons, electric field and hydromagnetic waves propagate simultaneously from the equatorial region in the magnetosphere to the mutually conjugate areas of the earth's surface. The auroral electrojets, SSC's, SI's and pc-5 pulsations show remarkable simultaneity and similarity between the conjugate areas. Their time-dependent parameters such as the form of frequency spectra, the dominant period of pulsations, the rise-time of SSC's, etc., are almost exactly the same in the conjugate stations. However, the correlation between amplitudes or magnitudes of these phenomena at the conjugate points is considerably smaller than that for the time-dependent parameters. The horizontal polarizations of SSC's, SI's and pulsations are the left-hand mode in the morning and right-hand one in the afternoon with an absolutely high statistical significance. These discussions are mostly based on the data from the conjugate pair of Syowa Station and Reykjavik and that of Macquarie Island and Alaskan stations. departmental bulletin paper